Shear-induced assembly of high-aspect-ratio graphene nanoribbon nanosheets in a confined microchannel: Membrane fabrication for ultrafast organic solvent nanofiltration. (May 2022) - Kim, Ji Hoon; Choi, Yunkyu; Kang, Junhyeok; Kim, Ju Yeon; Bae, Jun Hyuk; Kwon, Ohchan; Kim, Dae Woo
Abstract: One-dimensional graphene oxide nanoribbons (GONRs) were self-assembled into two-dimensional (2D) nanosheets using the shear and confinement effect during a slot-die coating process. An aqueous GONR suspension comprising nanostrings made of entangled GONRs at a concentration of 5 mg/mL was used. When the GONR suspension was injected into the microchannel of the slot-die coater, the GONR nanostrings self-assembled to form a nanosheet. The thickness of the GONR nanosheet could be controlled at the nanometer scale by adjusting the injection rate of the GONR suspension into the slot-die head, and the lateral dimension of the nanosheet was in the range of several tens of micrometers. The GONR nanosheets could be directly and continuously coated on a porous polymer support by the slot-die coating method. In particular, a 40-nm-thick GONR layer exhibited ultrafast organic solvent nanofiltration (OSN) with an isopropyl alcohol permeance of 679 LMH/bar and molecular weight cut-off of 961 Da, substantially surpassing the upper limit of the OSN performances of polymeric and 2D-material-based membranes. Highly efficient diafiltration of mixed organic molecules in an organic solvent is also feasible using this GONR membrane. Graphical abstract: Image 1